Required reading for the disenfranchised freshman - Lee, Kristen R. (Crown Books for Young Readers, 2022)
Upon arriving at the prestigious Wooddale University, seventeen-year-old Savannah Howard comes face-to-face with microaggressions and outright racism--but if she stands up for justice, will she endanger her future?